Metallo‐β‐lactamase structure and function. (16th November 2012) - Palzkill, Timothy
Abstract : β‐Lactam antibiotics are the most commonly used antibacterial agents and growing resistance to these drugs is a concern. Metallo‐β‐lactamases are a diverse set of enzymes that catalyze the hydrolysis of a broad range of β‐lactam drugs including carbapenems. This diversity is reflected in the observation that the enzyme mechanisms differ based on whether one or two zincs are bound in the active site that, in turn, is dependent on the subclass of β‐lactamase. The dissemination of the genes encoding these enzymes among Gram‐negative bacteria has made them an important cause of resistance. In addition, there are currently no clinically available inhibitors to block metallo‐β‐lactamase action. This review summarizes the numerous studies that have yielded insights into the structure, function, and mechanism of action of these enzymes.